2019
DOI: 10.1016/j.nicl.2019.101712
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain network measures are superior to vascular burden scores in predicting early cognitive impairment in post stroke patients with small vessel disease

Abstract: Objectives In this cross-sectional study, we aimed to explore the mechanisms of early cognitive impairment in a post stroke non-dementia cerebral small vessel disease (SVD) cohort by comparing the SVD score with the structural brain network measures. Method 127 SVD patients were recruited consecutively from a stroke clinic, comprising 76 individuals with mild cognitive impairment (MCI) and 51 with no cognitive impairment (NCI). Detailed neuropsychological assessments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
(60 reference statements)
3
37
1
Order By: Relevance
“…Network efficiency analyses also showed aberrant small-world topology (i.e., reduced global and local efficiency) in the ILA patients. These results are compatible with previous connectome-based studies on SVD (Lawrence et al, 2014 ; Tuladhar et al, 2016 , 2017 ; Du et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Network efficiency analyses also showed aberrant small-world topology (i.e., reduced global and local efficiency) in the ILA patients. These results are compatible with previous connectome-based studies on SVD (Lawrence et al, 2014 ; Tuladhar et al, 2016 , 2017 ; Du et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…ILA, ischemic leukoaraiosis. studies on SVD (Lawrence et al, 2014;Tuladhar et al, 2016Tuladhar et al, , 2017Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in keeping with previous studies. For instance, Du et al (2019) found that the global network efficiency of the brain structural network was significantly related to the cognitive state in patients with mild cognitive impairment caused by small vessel disease. Moreover, Heinen et al (2018) also found that global network efficiency of the brain structural network was related to cognitive functioning such as information processing speed, attention, and executive functioning in patients with mild cognitive impairment caused by small vessel disease.…”
Section: Altered Global Topological Properties In Sivcind Patients Comentioning
confidence: 99%
“…Moreover, the topological organization of whole-brain functional and structural networks could be employed to characterize some neurological and psychiatric disorders (Zhang et al, 2011;Shu et al, 2012;Zhu et al, 2016). Notably, one study recruited 127 small vessel disease patients which were comprised of 76 mild cognitive impairment patients and 51 normal cognitive patients; the results showed that global network efficiency was significantly correlated with cognitive state (p < 0.01) (Du et al, 2019). Another study (Heinen et al, 2018) considered the relationship between total small vessel disease burden score, global network efficiency and cognition; the results showed that global network efficiency was relevant to the performance on the information processing speed, attention and executive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…The physical exercise has become an acknowledged, safe, affordable, and important means of promoting health. Aerobic exercises, in particular, have been shown to have a beneficial effect on delaying aging, inhibiting apoptosis, managing hyperlipidemia, improving brain cognition, and treating dementia [1][2][3][4], which has been a boon for improving the life quality of human.…”
Section: Introductionmentioning
confidence: 99%